Pengaruh Tindakan Supervisi Terhadap Kepuasan Kerja Akuntan Pemula - Syamsul Hadi (Jurnal Akuntansi dan Auditing Indonesia, 2007)
The hypotheses of this research is junior auditor job satisfaction is low and automatically influencing the auditor’s professionalism. If the senior auditor has no attention on this problem, the whole auditor professionalism will be influenced. The indicator of senior auditor’s attention is senior auditor’s supervision. This research objective is to find the effect of the senior auditor’s supervision on the junior auditor job satisfaction.This research has 104 respondents. These research objects are Junior Auditors who are works less than 3 years. This research data are 104 Junior Accountant’s perception on Senior’s Supervision. Three aspect were detected, Leadership or and mentoring; working condition and job satisfaction. This research questionnaire set was taken from Patten (1995).The overall research conclusion is junior auditor’s job satisfactions was influenced by senior auditor’s supervision. Among the senior auditor’s supervision components, leadership and mentoring is significantly influencing the junior’s job satisfactions but the other two (working condition and audit engagement) are not.  Keywords: leadership & mentoring, engagement, working condition, job satisfaction